Fodder qualities of heterotic hybrids from intergeneric crosses between maize and eastern gamagrass - P. A. Panikhin; V. A. Sokolov (Труды по прикладной ботанике, генетике и селекции, 2020)
Green biomass yield and fodder qualities are the starting point in the choice of forage crops. Maize, as a plant with the C4 pathway of photosynthesis, is highly efficient in transforming the energy of light into chemical bond energies, which ultimately leads to the highest yield per unit area of cultivated land. Its grain and green biomass possess good fodder qualities and are actively used in feed rations for cattle, smaller ruminants, and poultry. Eastern gamagrass (Tripsacum dactyloides L.), a wild relative of maize, is widespread over the plains of North and South Americas. To date, it has received universal recognition among breeders as a forage and fodder crop. More than 10 commercial cultivars have already been developed and cultivated in the United States. Eastern gamagrass is a C4 plant as well, characterized by high yield and high feed value of hay. We decided to combine in our research economically valuable qualities of this plant by developing apomictic intergeneric hybrids. This paper presents the results obtained in the process of assessing fodder qualities of apomictic maize × Tripsacum hybrids, where two maize genomes from the lines participating in hybrid selection for F1 seeds were added to the 36 chromosomes of eastern gamagrass. The maize × Tripsacum hybrid forms, produced during a number of years, persistently demonstrated an apomictic reproduction pattern and heterosis in green biomass productivity. Zootechnical analysis of plant samples showed that the hybrids, in which chromosomes of the lines used in commercial seed production to obtain heterosis in F1 had been added to the 36 chromosomes of eastern gamagrass, exceeded in their biochemical indicators the plants, in which 20 chromosomes from one of the maize lines earlier used in hybridization at our laboratory had been added. A theoretical estimate of green biomass yield calculated per hectare for the maize × Tripsacum hybrids is about 65 tons.